Analisis Pengaruh PAD, DAU, DAK, DBH, dan PDRB terhadap Belanja Modal pada Pemerintah Daerah Kabupaten/Kota di Provinsi Jawa Tengah - Zulafah, Annida; Arifin, Agus; Binardjo, Goro (Lingka Ekonomika, 2023)
Regional expenditure carried out by the Regional Government is still of low quality, only 30 percent of the APBD (Anggaran Pendapatan dan Belanja Daerah) has a direct impact on the public. Regional expenditure is used more for operational expenditure which is generally less productive, while capital expenditure is the least compared to other expenditure, even though their use can be felt directly by the public. The realization of capital expenditure in Central Java Province is still below 30 percent, it has not yet reached the target according to the direction of the Ministry of Home Affairs. The purpose of this study is to analyze the effect of PAD (Pendapatan Asli Daerah), DAU (Dana Alokasi Umum), DAK (Dana Alokasi Khusus), DBH (Dana Bagi Hasil), and PDRB (Produk Domestik Regional Bruto) on capital expenditure. The data analysis technique in this study uses panel data regression analysis. The results of this study indicate that: 1) PAD and DBH have a positive effect but not significant on capital expenditure, 2) DAU and DAK have a positive and significant effect on capital expenditure, and 3) PDRB has a negative and significant effect on capital expenditure. The implication of this research is that Regional Government must optimize the extraction of resources that contribute to PAD and DBH. The Regional Government further increase the DAU and DAK budgets allocated to the capital expenditure budget to improve public service. Regional Government can minimize unnecessary routine expenditure, more allocated to capital expenditure in order to improve people’s welfare and encourage economic development and community self-sufficiency in a sustainable manner.